Effect of Carbohydrate Type and Phenotype on the Quality of Post-Thawing Frozen Semen of KUB Chicken - Maghfira Maghfira; Ni Wayan Kurniani Karja; R. Iis Arifiantini; Tike Sartika (Indonesian Center for Animal Research and Development (ICARD), 2023)
The superior Balitbangtan Kampung Chicken (KUB) chickens have different phenotypes. It was reported that the chicken phenotype was related to semen quality. This study aimed to determine the post-thawing characteristics and quality of KUB chicken semen with different phenotypes frozen in Ringer's lactate egg yolk (RLEY) diluent with the addition of fructose or glucose. Semen was collected using the massaging method from 20 KUB chickens with a single comb phenotype and black or dark brown feather color with a red feather neck (SCNR), green-black single comb with white feather neck collar (SCNW), pea comb and black feathers or dark brown fur with a red neck (PCNR), and a green-black pea comb with a white neck (PCNW). Semen from each chicken phenotype was divided into three parts or frozen in three types of diluents: RLEY, RLEY+fructose (RLEYF), and RLEY+glucose (RLEYG). The highest sperm motility was found in the diluent with the addition of glucose in the SCNR and PCNW phenotypes (P0.05). The highest sperm viability was shown in the RLEYG diluent in the PCNW phenotype (P0.05). The highest abnormality was found in the RLEY and RLEYF diluents in the SCNW, PCNR, and PCNW groups, whereas in the RLEYG group, it was only found in the PCNR group. From the results of this study, it can be concluded that the type of glucose and chicken phenotype influences the quality of post-thawing semen. The best is found in diluents with glucose attachments in the SCNR phenotype.